Living law politics and legality beyond the law - Chignola, Sandro 1961- (Routledge, 2025)
"This book offers a radical new understanding of law, beyond the confines of its formalization by the state. The book takes off from the late work of Gilles Deleuze and Michel Foucault, for whom law and its institutions came to be liberated from an ideological perspective that had treated them as sterile instruments for the reproduction of domination. Engaging its continental history, it addresses the concept of law, not merely as a 'command', but as the result of a much more complex legal operation aimed at dynamically stabilizing the social relations of a community. The book thus sidesteps the usual legal-political focus on those - from Hobbes to Schmitt - who have contributed to the categorical scheme of the modern state, and with it questions of political representation, sovereignty, the rigid distinction between public law and private law, and so on, as it pursues an alternative theoretical trajectory through Ravaisson, Tarde, and Hauriou. Politics, the book maintains, can be no longer be treated simply through the state form. And, relatedly, the law must be seen as a living law: a law that cannot be treated exclusively in formal terms, but must be taken as a grammar capable of articulating a politics of process, relationality, and innovation. Reconceived as such, law can then circumvent the aporias that arise when society is viewed as a private company, and the state seen as the bearer of the only possible means of formalizing its relationships. At the intersection of law and political theory, this book will speak to scholars and others with interests in both these areas, and especially those concerned with the limits of both conventional and critical approaches to law"--
Keywords: Rechtssoziologie; Politische Philosophie; Rechtsphilosophie; Law / Philosophy; Rule of law; Law / Political aspects; Règle de droit; Droit / Aspect politique